Maize Self-Sufficiency Projections for 2050: Challenges and Opportunities in Nepal - Khaniya, Sachin; Karki, Rojan; Kafle, Sagar (Journal of Nepal Agricultural Research Council, 2025)
Maize is a vital staple crop in Nepal, crucial for food security, rural livelihoods, and animal feed. However, challenges such as low yield, limited use of high-yield varieties, climate impacts, and pest infestations hinder production, contributing to rising import dependency. This study examines current maize production, identifies challenges, and explores the potential for achieving self-sufficiency by 2050. Using data from secondary sources, government reports, expert consultations, projection models were developed based on population and GDP growth scenarios. Regression analysis using the Prais-Winsten model estimated the relationship between maize production, demand, self-sufficiency ratio (SSR), and import dependency ratio (IDR). Results indicate production may increase from 3.49 million metric tons in 2030 to 4.67 million metric tons in 2050, while demand is projected to rise from 4.69 million to 6.07 million metric tons. This growing gap could lead to a reduction in SSR from 52% in 2030 to 2% by 2050. The study highlights the urgent need for improved pest management, technological advancements, and increased productivity to reduce imports and achieve sustainable self-sufficiency by 2050.